Weed flora of Sugarcane (Saccharum officinarum L.) Crop Cultivated on High Fertile Soil of District Charsadda-Pakistan - Rahmdad Khan; Abuzar Shoukat; Abbas Khan; Muhammad Shabir Akbar; Muhammad Haris (TERRA : Journal of Land Restoration, 2022)
Sugarcane is the major crop of district Charsadda-Pakistan and weeds infestation is the most problematic factor responsible for low yield in sugarcane. For the purpose a field experiment was conducted to find out the important and most problematic weeds of Sugarcane crop using quadrate method in different sugarcane fields at DistrictCharsadda, Khyber Pakhtunkhwa, Pakistan. The data was collected during summer season,2021. Based on spatial data it is concluded that Cyperus rotundus L., Parthenium hysterophorus L., Trianthema portulacastrum L., Euphorbia helioscopia  L., Convolvulus arvensis  L., Brachianreptans (L.)., Amaranthus viridusL., Physalis minima  L., Dactydocteniumaegyptium(L)., Amaranthus spinosusL., Portulaca  oleracea  L.,CynodondactylonL. and  Solanum nigrum  L., were the most abundant weeds of the studied fields. The relative weed densities (%) and relative frequencies (%) of all these weeds were calculated to quantify their importance values in descending order of their percentages as following: P.hysterophorus, T.portulacasrum, C.rotundus,  E. helioscopia. C. arvensis, B.reptans, A.viridus, and S. nigrum. Similarly, the highest (35.1%) importance value recorded for C. rotundus and declared the most competitive weed of sugarcane at district Charsadda. The control of C. rotundus recommended for the farmers of the area for the outmost yield of sugarcane.